2021
DOI: 10.1021/acssuschemeng.1c04305
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading of Aqueous Bioethanol to Higher Alcohols over NiSn/MgAlO Catalyst

Abstract: The calorific value and cetane number of C4+ long-chain higher alcohols are similar to those of diesel, blending with which can significantly reduce pollutant emissions from diesel engines. Direct upgrading of aqueous bioethanol derived from the biomass fermentation to higher alcohols faces the challenge of efficient catalysts with excellent catalytic activity and hydrothermal stability. Herein, NiSn/MgAlO catalysts prepared by loading Ni and Sn into hydrotalcite through coprecipitation and ion exchange method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
(82 reference statements)
1
4
0
Order By: Relevance
“…However, when the reaction temperature further increases to 210 °C, the conversion rate only a slight rise and reaches the highest value at 230 °C. The results show that high reaction temperature is favorable to ethanol conversion, which is consistent with literature reports . The ethanol dislocation in the reaction mixture is conducive to the formation of gaseous products.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, when the reaction temperature further increases to 210 °C, the conversion rate only a slight rise and reaches the highest value at 230 °C. The results show that high reaction temperature is favorable to ethanol conversion, which is consistent with literature reports . The ethanol dislocation in the reaction mixture is conducive to the formation of gaseous products.…”
Section: Resultssupporting
confidence: 91%
“…The results show that high reaction temperature is favorable to ethanol conversion, which is consistent with literature reports. 47 The ethanol dislocation in the reaction mixture is conducive to the formation of gaseous products. It is worth noting that the selectivity of aldehydes is high at lower temperatures below 230 °C, which indicates that the hydrogenation reaction of aldehyde intermediates is relatively inert at mild temperatures.…”
Section: Effect Of Carbonizationmentioning
confidence: 99%
“…The hydrogen transfer reactions, i.e., dehydrogenation of ethanol and hydrogenation of crotonaldehyde to n -butanol, are key elementary steps in the conversion of ethanol to n -butanol. Therefore, the reduction and hydrogen storage ability of the catalysts were first studied. Figure A shows the H 2 -TPR curves of NiCeO 2 /CNTs and NiCeO 2 @CNTs catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, LDH composite materials involving different transition metals or noble metals , have also been widely used, especially first-row transition metals or metal alloys, which can enhance the hydrogenation reaction. , On the other hand, Gao et al reported that the balance of moderate acidic–basic sites on the surface of Mg–Al oxide or Mg–Al LDH-derived oxides is important and that the catalytic pathway of ethanol condensation can be directed toward BD production. , For BD production from ethanol condensation, magnesium silicate (MgO–SiO 2 )-derived materials have been largely investigated in the past, and recent developments have focused on the nature of active sites, especially the interactions among MgO, SiO 2 , and supported metal particles, which have been vigorously discussed. ,, Interestingly, the addition of amorphous silica, as previously mentioned, was treated as more than a feasible support. With the nature of silanol groups, silica could provide the acid sites necessary for dehydration, although silica was critically found to facilitate acetaldehyde condensation to crotonaldehyde for both the Lebedev and Ostromislensky processes. , Thus, the role of amorphous silica might still remain uncleared for further investigation.…”
Section: Introductionmentioning
confidence: 99%